Nitroimidazole-refractory giardiasis: a growing problem requiring rational solutions. (January 2018) - Carter, E.R.; Nabarro, L.E.; Hedley, L.; Chiodini, P.L.
Abstract: Background: Giardia intestinalis is microaerophilic diarrhoea-causing protozoan common in countries with suboptimal sanitation. Standard treatment is with nitroimidazoles, but a growing number of refractory cases is being reported. Treatment failure has become increasingly prevalent in travellers who contract giardiasis in Asia. Clinicians are increasingly falling back on second-line and less well-known drugs to treat giardiasis. Aims: To review nitroimidazole-refractory G. intestinalis infection, examine the current efficacy of standard therapeutic agents, consider potential resistance mechanisms which could cause treatment failure and describe the practical aspects of managing this emerging clinical problem. Sources: A PubMed search was conducted using combinations of the following terms: refractory, Giardia, giardiasis, resistance and treatment. Articles on the pharmacotherapy, drug resistance mechanisms and use of alternative agents in nitroimidazole-refractory giardiasis were reviewed. Content: We review the standard drugs for giardiasis, including their efficacy in initial treatment, mode of action and documented in vitro and in vivo drug resistance. We assess the efficacy of alternative drugs in nitroimidazole-refractory disease. Existing data suggest a potential advantage of combination treatment. Implications: An optimal treatment strategy for refractory giardiasis has still to be determined, so there is no standard treatment regimen for nitroimidazole-refractory giardiasis. Further work on drug resistance mechanisms and the use of drug combinations in this condition is a priority.